Legal Protection for Victims of Illicit Banks Under the Guise of Cooperatives Requires Indonesian Government Intervention - Jety Widjaja; Yuwono Prianto (Sociological Jurisprudence Journal, 2023)
Illicit Bank under the guise of a Cooperative is a form of illegal investment in Indonesia. Cooperatives that do not carry out their principles and functions according to the Cooperative Regulation Law no. 25 of 1992, collecting public funds illegally, and ultimately failing to return the funds deposited by its members is an indication of Illicit Bank. The Indosurya Cipta Savings and Loans Cooperative was an illicit bank under the guise of a cooperative that was found as the biggest fraud case in Indonesia, affected 23,000 victims and a loss of 106 trillion rupiahs. KSP Indosurya Cipta was charged with Article 46 Paragraph 1 of Law no. 10 of 1998 concerning Amendments to Law no. 7 of 1992 concerning Banking and Money Laundering. Normative legal research was conducted to analyze the importance of the government's role in providing legal protection for tens of thousands of victims of this illicit bank. After the court decision to refund the victim's deposit funds through the homologation process two years ago failed again, the confiscation of criminal assets (TPPU) of the Founder and two other perpetrators requires certainty and different legal settlements in order to compensate the victims, not only as evidence to punish the perpetrators of the crime. The intervention of the Government of Indonesia and related agencies is important to restore the confidence of the Indonesian people in the existence of the law and the protection of investment in the legality of legal entities such as cooperatives.